Post-activation Potentiation Versus Post-activation Performance Enhancement in Humans: Historical Perspective, Underlying Mechanisms, and Current Issues - Blazevich, Anthony J.; Babault, Nicolas (Frontiers in Physiology, 2019)
Post-activation potentiation (PAP) is a well-described phenomenon with a short half-life (~30 s) that enhances muscle force production at submaximal levels of calcium saturation (i.e. submaximal levels of muscle activation). It has been largely explained by increased myosin light chain phosphorylation occurring predominately in type II muscle fibers, and can be tested in humans by measuring muscle twitch force responses to a bout of muscular activity. However, enhancements in (sometimes maximal) voluntary force production detected several minutes after high-intensity muscle contractions have also been observed, and which are also most prominent in muscles with a high proportion of type II fibers. This has recently been described as post-activation performance enhancement (PAPE) by some authors because the phenomenon appears to be distinct from PAP. Importantly, the time course of myosin light chain phosphorylation (PAP) does not match that of PAPE and, unlike PAP, changes in muscle temperature, muscle/cellular water content, and muscle activation may at least partly explain PAPE. In fact, since PAPE is often undetectable at time points where PAP is maximal, or at least substantial, it may be questioned whether PAP provides an important performance enhancement benefit under most conditions in vivo in humans. Equally, minimal evidence has been presented that PAPE is of significant practical importance in cases where multiple physiological processes have already been upregulated by a preceding, comprehensive, active muscle warm-up. Given that confusion exists among researchers and clinicians with respect to phenomena that acutely enhance muscle function in humans, including both traditional warm-up effects and post-activation performance enhancements, the first purpose of the present review is to describe the history of PAP and PAPE research to highlight their potentially different underpinnings and to correct errors relating to the use of these terms. To further investigate the possibility of these phenomena being distinct as well as to better understand their potential function benefits, possible mechanisms underpinning their effects will be subsequently examined. Finally, research design issues will be addressed which might contribute to confusion relating to PAP/PAPE effects, before the contexts in which these phenomena may (or may not) benefit voluntary muscle function are considered.